Evaluation of empirical antibiotic usage and cost analysis of patients with nosocomial pneumonia in ICU of RSUP Dr. Sardjito, yogyakarta - Minar Paskah Lianti Manik; Rizka Humardewayanti Asdie; Ika Puspitasari (Faculty of Medicine, Public Health, and Nursing Universitas Gadjah Mada and Indonesian Pharmacologist Association or Ikatan Farmakologi Indonesia (IKAFARI), 2020)
The rationality of antibiotic usage has an implication on the therapeutic quality and antimicrobial resistance control. Qualitative and quantitative evaluation of this rationality becomes one quality indicator of hospitals' antimicrobial resistance programs. Therefore, this study aims to determine the relationship between the rationality of antibiotic usage with clinical outcomes and the total cost in nosocomial pneumonia patients treated in the Intensive Care Unit (ICU). The method used was descriptive-analytic observational research with a cross-sectional design analysis, and data were collected retrospectively from the medical and financial record of patients with inclusion criteria. The data were then analyzed descriptively using the Gyssens flowchart. Fisher statistical test was conducted to analyze the relationship between rationality data and therapeutic outcomes. Furthermore, the Mann Whitney statistical test was conducted to examine the relationship between rationality data and the cost, while the paired t-test was conducted to analyze the resistance pattern. The results showed that antibiotic usage in patients with nosocomial pneumonia at the ICU of RSUP Dr. Sardjito was irrational and rational by 30.21% (29 regimens) and 69.79% (67 regimens) respectively. This rationality has a relation with clinical outcome based on Fisher test with p-value = 0.001 (p <0.05). Considering these results, the antibiotics cost both in the rational and irrational category has no significant difference with the p-value of 0.90 (p<0.05).